Avaliação da atividade antimicrobiana e do mecanismo de ação do óleo essencial extraído da casca de frutos da Hymenaea courbail L. - Sales, Gleilton Weyne Passos (2014)
Jatobá (Hymenaea courbaril l.) has an extensive history of use by natives of tropical forests, its fruits are composed of essential oils, tannins, bitter substances, resinous materials and pectic, starch and sugars. The objective of this study was to evaluate the antimicrobial activity of the essential oil extracted from the peel of fruits of Hymenaea courbaril l. (OEHc) and its mechanism of action on OSSA reference strains S. aureus (S. aureus ATCC 6538P and S. aureus 14458). For the evaluation of antimicrobial activity antimicrobial potential were determined from OEHc Inhibitory Concentrations (MIC) and Minimum Lethal (CLM) from OEHc, the effect of time of exposure to OEHc, OXA and OEHc associations-OXA, OEHc modulator effect on activity of antibiotics (ATB) for clinical use, and the OEHc action on exponential and stationary phases of growth and in growth stationary phase in the presence of chloramphenicol. The OEHc action mechanism was verified by crystal violet uptake, release of genetic material, determination of potassium ion efflux and for assessing the microbial morphology by atomic force microscopy. It was also evaluated the action of sub-inibitórias concentrations of OEHc on expression of virulence factors (catalase, coagulase, DNAse, lipase, and hemolysin) and stability of antimicrobial activity of OEHc at different pH. OEHc inhibited the growth of S. aureus strains ATCC 6538P (CIM = CLM = 2.5 mg/mL) and S. aureus ATCC 14458 (CIM = 2.5 mg/mL; CLM = 5 mg/mL). The CLM from OEHc was able to derail the OSSA strains tested in 8 (S. aureus ATCC 6538P) and 24 hours (S. aureus ATCC 14458) and the CIM inhibited the growth of S. aureus ATCC 14458 until 48 hours of exposure. The modulatory action of the antibiotic activity of OEHc clinical use ranged with the ATB and with the strain tested. OEHc associations-OXA tested was found a predominance of synergistic effects and indifferent to the OSSA strains tested. The OEHc was able to reduce the number of viable cells at all stages microbial growth. Its greater efficiency in the presence of CLO suggests a mechanism of action independent of the cellular metabolism. The OEHc was able to promote the increased uptake of crystal violet, the release of genetic material and the efflux of potassium ions, causing also changes in bacterial morphology, suggesting that its target of action is the cell wrap. However, the inhibition of the expression of virulence factors can indicate the participation of other targets on OEHc action, as the synthesis of macromolecules. The antimicrobial activity of OEHc about strains OSSA is potentized in alkaline pH. The results show that the OEHc has a good antimicrobial activity on the species Gram-positive S. aureus, with action mechanisms mediated by the occurrence of damage in microbial wrap with loss of intracellular material and inhibition of the synthesis of macromolecules, revealing its synergistic modulator effect when associated with oxacillin and other antibiotics of clinical use.